Beta-blockers in post-acute myocardial infarction patients: Drug prescription patterns from 2018 to Italy’s first wave of the COVID-19 pandemic - Olmastroni, Elena; Galimberti, Federica; Catapano, Alberico L.; Tragni, Elena; Casula, Manuela (Frontiers in Pharmacology, 2022)
Background Major guidelines recommend the initiation of a beta-blocker therapy after an acute myocardial infarction (AMI). We aimed to map the treatment pathway of beta-blockers for AMI survivors during the first wave of COVID-19 pandemic in Italy and to investigate predictors for treatment non-initiation. Methods Healthcare utilization databases of Lombardy Region were investigated. Subjects aged ≥18 years who were hospitalised with AMI in the period February-March-April of 2018, 2019, and 2020 were included, and followed for 30 days from the discharge date, to investigate whether they presented a first prescription of beta-blockers. A multivariate logistic model was performed to evaluate the effect of several covariates on the probability of not receiving a post-AMI beta-blocker therapy. Results The cohorts comprised 2259, 2383, and 1932 individuals who were hospitalised with AMI in the 3-month period in 2018, 2019, and 2020, respectively. Overall in 2020, about 58-60% of individuals with AMI received a prescription of beta-blockers within one month after the discharge. A continuous decreasing trend over time was observed. Men were 30% more likely to start the treatment than women, increasing age was associated with significant increasing probability of not receiving a post-infarction beta-blocker therapy, while having received an antihypertensive or lipid-lowering treatment, or having been hospitalized for heart failure prior to the AMI hospitalization reduced the likelihood of not being treated with beta-blockers. Conclusions The initiation of beta-blocker treatment after AMI remains an under-prescribed practice, that does not seem to have been further affected by the first wave of the COVID-19 pandemic.